MUFRADAT LEARNING STRATEGY WITH MULTIPLE INTELLIGENCES-BASED CLASSROOM MANAGEMENT: CASE STUDY AT SD AL-KAUTSAR MALANG - Rizka Widayanti; Dian Febrianingsih (IAIN Batusangkar, Indonesia, 2020)
This paper aims to describe the concept of mufradat learning strategies at SD Al-Kautsar Malang which are packaged using multiple intelligences-based classroom management and to understand the factors that influence the success of the learning strategy in each class. The author used descriptive qualitative research methods. The results showed that SD Al-Kautsar has organized a learning program well which is marked by the application of a mufradat learning strategy based on multiple intelligences class management by producing various mufradat learning strategies, as well as the factors that influence the success of mufradat learning at SD Al-Kautsar including strong funding, reliable human resource management, as well as facilities and infrastructure factors.Penelitian ini bertujuan untuk mendeskripsikan konsep strategi pembelajaran mufradat yang diterapkan di SD Al-Kautsar Malang yang dikemas dengan menggunakan manajemen kelas berbasis kecerdasan majemuk dan untuk memahami faktor-faktor yang mempengaruhi keberhasilan strategi pembelajaran di setiap kelas. Peneliti menggunakan metode penelitian kualitatif deskriptif. Hasil penelitian menunjukkan bahwa SD Al-Kautsar telah menyelenggarakan program pembelajaran dengan baik yang ditandai dengan penerapan strategi pembelajaran mufradat berbasis manajemen kelas kecerdasan majemuk dengan menghasilkan berbagai strategi pembelajaran mufradat, serta faktor-faktor yang mempengaruhi keberhasilan pembelajaran mufradat di SD Al-Kautsar adalah pendanaan yang kuat, manajemen sumber daya manusia yang handal, juga faktor sarana prasarana.